2019
DOI: 10.1002/ejoc.201801369
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Double Friedel‐Crafts Alkylation of Tetrahydroquinolines Under Aqueous Conditions: Efficient Synthesis of gem‐Diarylacetic Esters

Abstract: An efficient double Friedel‐Crafts alkylation strategy has been developed for the synthesis of 2,2‐bis(1,2,3,4‐tetrahydroquinolin‐6‐yl)acetates from N‐arylglycine esters using 10 mol‐% CuI in water as solvent. The reaction presumably involves α‐C‐H bond functionalization and concurrent nucleophilic substitution of the N‐arylglycine esters producing double Friedel‐Crafts alkylation products. The reaction protocol is successfully extended for N‐methyl aniline and indole nucleophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The residue was purified by recrystallization from EtOAc and silica gel column chromatography (EtOAc/hexane = 1/6−1/3) to give 7 (1.04 g, 98% yield) as a pale yellow solid: IR (KBr) 3152, 1692, 1422, 1377, 1175, 669 cm −1 ; 1 H NMR (600 MHz, CDCl 3 ) δ 8.13 (d, J = 1. Methyl 2,2-Bis(6-bromo-1H-indol-3-yl)acetate (6). A mixture of 7 (853 mg, 1.0 mmol) in 10% NaOH(aq) (5.0 mL) and MeOH (10 mL, 0.1 M) was stirred at reflux temperature under an argon atmosphere for 9 h. After the reaction mixture was cooled to rt, it was quenched with 1 M HCl; then brine was added to the mixture, and the whole was extracted with EtOAc.…”
Section: 5-bis(6-bromo-1-tosyl-1h-indol-3-yl)-13-dimethylpyrimidine-2...mentioning
confidence: 99%
See 1 more Smart Citation
“…The residue was purified by recrystallization from EtOAc and silica gel column chromatography (EtOAc/hexane = 1/6−1/3) to give 7 (1.04 g, 98% yield) as a pale yellow solid: IR (KBr) 3152, 1692, 1422, 1377, 1175, 669 cm −1 ; 1 H NMR (600 MHz, CDCl 3 ) δ 8.13 (d, J = 1. Methyl 2,2-Bis(6-bromo-1H-indol-3-yl)acetate (6). A mixture of 7 (853 mg, 1.0 mmol) in 10% NaOH(aq) (5.0 mL) and MeOH (10 mL, 0.1 M) was stirred at reflux temperature under an argon atmosphere for 9 h. After the reaction mixture was cooled to rt, it was quenched with 1 M HCl; then brine was added to the mixture, and the whole was extracted with EtOAc.…”
Section: 5-bis(6-bromo-1-tosyl-1h-indol-3-yl)-13-dimethylpyrimidine-2...mentioning
confidence: 99%
“…An efficient protocol for the synthesis of bisindolylacetic acids is quite rare. 6 In 2015, Lam and co-workers reported a novel strategy for the synthesis of 5-aryl barbituric acids based on the rhodium(II)-catalyzed C−H functionalization of indoles with diazo barbituric acids. 7 However, this umpolung transformation lacks a double indolization due to the intrinsic character of the diazo compounds.…”
mentioning
confidence: 99%
“…[24] Henry-Ritter reactions are reported to access one pot synthesis of N-(β-Nitro) amides from aldehyde, nitro compounds and nitriles. [25] In continuation of our research efforts to explore CÀ H functionalisation reactions for the construction of CÀ C, [26,27] CÀ N [28,29] and CÀ O [30,31] bonds in open flask conditions, we aimed to investigate the one-pot multicomponent reaction for the synthesis of amides. Considering the importance of the complex amide products, we assumed that readily available and less expensive nitriles would be an excellent amidation tool in tandem Ritter reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[31] J. Zhou et al reported a catalytic Ritter reaction of 3-alkyl and 3-aryl-3-hydroxy oxindoles and nitriles for the synthesis of 3-substituted-3-aminooxindoles (Figure 2). [32] As a part of our ongoing research program on CÀ H functionalizations for the construction of CÀ C [33,34,35] and CÀ N [36,37,38,39] bonds, we became interested in Ritter and Mannich reactions and envisioned that multicomponent Ritter reaction could affect the single step synthesis of diverse and complex 2oxindole derivatives by C3 functionalization of isatin. In this paper, we report the development of novel and efficient acid catalyzed synthesis of variety of sterically crowded diamide products, 3-aryl-3'-amidooxindoles in one pot MCR directly from commercially available isatin, nucleophile, and nitrile (Figure 2).…”
Section: Introductionmentioning
confidence: 99%